EFEKTIVITAS BANTUAN BAGI PELAKU USAHA MIKRO DI KELURAHAN MALALAYANG SATU BARAT KECAMATAN MALALAYANG KOTA MANADO - KAAWOAN, EIRENE; RURU, JOORIE; KOLONDAM, HELLY (Sam Ratulangi University, 2022)
The purpose of this study was to determine the effectiveness of Assistance for Micro Business Actors(BPUM) in Malalayang Satu Barat Village, Malalayang District, Manado City. By using qualitativeresearch methods, this research focuses on the effectiveness of providing assistance to the community inthe West Malalayang Satu Village. The research study was conducted using the theory of Campbell J.P (inStarawaji 2009:121) which said that the measurement of effectiveness in general can be seen from:Program success; Target Success; Satisfaction with the Program; Achievement of Program Objectives;and Input and Output Levels. From the results of the study, it was found that the success of theGovernment Assistance Program for Micro Business Actors in Malalayang Satu Barat Village had notbeen successful as a whole, in terms of the distribution of assistance to recipients has been runningaccording to the mechanism regulated by the government and the appointed bank, but there are still someproblems that need to be addressed. the government must answer and resolve it, such as beneficiaries whodo not have businesses, there are also those who should have the right but their names are not listed aspotential beneficiaries.Keywords: Effectiveness; Government Assistance; Micro Business